2018
DOI: 10.1002/ajmg.a.40526
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations of mitochondrial dysfunction in Prader–Willi syndrome

Abstract: Prader-Willi syndrome (PWS) is a complex multi-system disorder due to errors in genomic imprinting with severe hypotonia, decreased muscle mass, poor suckling, feeding problems and failure to thrive during infancy, growth and other hormone deficiency, childhood-onset hyperphagia and subsequent obesity. Decreased energy expenditure in PWS is thought to contribute to reduced muscle mass and physical activity but may also relate to cellular metabolism and disturbances in mitochondrial function. We established fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…A recent report of gene expression in post-mortem hypothalamic tissue in PWS reported a transcriptomic profile similar to that seen in neurodegenerative conditions and the aging brain, with downregulated genes mainly found in neuronal cells and involved in neurogenesis and synaptic plasticity, while upregulated genes were mainly microglial and associated with inflammatory responses ( Bochukova et al, 2018 ). In addition, a recent small study found decreased ex vivo mitochondrial function in fibroblast cell lines from patients with PWS (especially in those with deletion genotype) that might also play a pathogenic role in accelerated brain aging if also seen in other cell types ( Butler et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of gene expression in post-mortem hypothalamic tissue in PWS reported a transcriptomic profile similar to that seen in neurodegenerative conditions and the aging brain, with downregulated genes mainly found in neuronal cells and involved in neurogenesis and synaptic plasticity, while upregulated genes were mainly microglial and associated with inflammatory responses ( Bochukova et al, 2018 ). In addition, a recent small study found decreased ex vivo mitochondrial function in fibroblast cell lines from patients with PWS (especially in those with deletion genotype) that might also play a pathogenic role in accelerated brain aging if also seen in other cell types ( Butler et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…PWS2 possessed a single autosomal recessive gene variant ( TTC19 ) involving mitochondrial complex III deficiency which may have functional relevance in an individual with PWS. Recently, mitochondrial dysfunction has been reported in living cells from individuals with PWS (Butler, Hartin et al, ; Butler, Hossain et al, ). This specific gene variant has not been associated with a disorder and is classified as having an uncertain clinical significance.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent PWS frequency data shows the 15q11‐q13 deletion is lower at 60% of cases while mUPD15 is higher at 36% than previously reported, potentially due to advanced maternal age. Imprinting center defects including microdeletions or failure to establish the correct methylation pattern (epimutations) are seen in the remaining 4% of individuals with PWS (Butler, Hartin et al, ; Butler, Hossain, Tessman, & Krishnamurthy, ). Earlier literature suggested that 15%–20% of those with PWS and IC defects are caused by a microdeletion in the IC (Buiting et al, ; Sutcliffe et al, ), associated with the 50% recurrence risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormone deficiencies are also recognized in PWS along with a lower metabolic rate. 19 Confounding predisposing factors for developing rectal damage and prolapse besides chronic constipation may include obsessivecompulsions, self-stimulation and self-injury, rectal picking, and digital manipulation along with a lower pain sensation compared with the general population. 3 Skin picking behavior in PWS can be pronounced leading to significant comorbidities including bleeding and loss of tissue at the wound sites with infections and ulcerations requiring medical and/or surgical intervention.…”
Section: Clinical Manifestations In Prader-willi Syndrome Predisposinmentioning
confidence: 99%